2020
DOI: 10.1108/cdi-12-2018-0299
|View full text |Cite
|
Sign up to set email alerts
|

When and why do negative organization-related career shocks impair career optimism? A conditional indirect effect model

Abstract: PurposeThis study investigates when and why negative organization-related career shocks affect career optimism, which is a positive career-planning attitude. The indirect effect of negative organization-related career shocks on career optimism via job insecurity and the role of perceived organizational career support as a first-stage moderator were investigated.Design/methodology/approachThree-wave time-lagged data from a sample of 728 employees in Switzerland was used. Time-lagged correlations, an indirect ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 96 publications
(266 reference statements)
0
29
1
Order By: Relevance
“…In the first article, Hofer et al (2021) conduct a three-wave quantitative study among 728 Swiss employees to examine the role of career shocks in career optimism. They find that a negative organization-related career shock, measured using an item from Seibert et al (2013), can lead to perceptions of increased job insecurity.…”
Section: Lessons Learned From the Special Issuementioning
confidence: 99%
“…In the first article, Hofer et al (2021) conduct a three-wave quantitative study among 728 Swiss employees to examine the role of career shocks in career optimism. They find that a negative organization-related career shock, measured using an item from Seibert et al (2013), can lead to perceptions of increased job insecurity.…”
Section: Lessons Learned From the Special Issuementioning
confidence: 99%
“…A partial dataset ( N = 728) was used in Hofer et al. (2021). There is no overlap in the used constructs.…”
mentioning
confidence: 99%
“…Previous scholarships on the subject matter have well documented the positive linear relationship between nature of shock and eventual outcome (e.g. Hofer et al, 2020). This implies that positive career shocks are related to positive outcomes, while negative career shocks are related to negative outcomes (e.g.…”
Section: Positive Career Shocks and Cdsementioning
confidence: 97%
“…Recent scholarships have suggested the inclusion of moderating variables while examining the relationship of career optimism with related variables of interest (Eva, et al, 2020). Advancingly, Hofer et al (2020) have suggested incorporating the key resources (e.g. personal resources, career resources, energy resources) as moderators to check their effect on career attitudes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation